Prevalencia de enfermedades profesionales en el personal de enfermería del servicio de clínicas quirúrgicas, emergencia y quirófano del Hospital General Puyo. Año 2013 -2014 - Peñafiel Mejía, Yajaira Abigail (2015)
This research work was conducted in Puyo General hospital, the nursing staff in the area of surgical clinics, emergency surgery, in order to establish demographic, social and occupational characteristics of staff, determine the prevalence of occupational diseases, identify existing risk factors and identify the consequences of occupational diseases; while performing activities that encouraged and were aimed at improving the practice of career nurses; purposes of preventing any kind of disease or accidents can be generated and the work occurs. The research design corresponds to transverse, descriptive literature, quantitative field, Fixed techniques for data collection such as the survey with its instrument, observation with the respective guide were used. Among the collected results of the research showed that there staff who are suffering or have suffered occupational diseases; of the most common of which was evident was neck pain with a percentage of 46.66%. It was also determined that the nursing staff if you are exposed to risk factors, such as lack of application of body mechanics and biosafety standards, work pressure and overload of work in your workday; which are the main causes that trigger the manifestation of occupational diseases. Besides the consequences of identified risk factors were observed. Keywords: Occupational disease, nurses, clinical and surgical services, emergency services, surgical services